Thermal shrinkage material for cable and preparation method of thermal shrinkage material
By introducing allyl-containing functionalized ring triphosphazene derivatives into the heat shrinkable material for cables, a tight and stable crosslinking network is formed, which solves the shortcomings of traditional cable accessories in terms of flame retardancy, thermal stability and high temperature resistance, and has achieved significant improvements in the mechanical properties, heat resistance and flame retardancy of the material.
Patent Information
- Application Number
- CN202510082843.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
Traditional cable accessories have obvious shortcomings in flame retardancy, thermal stability and high temperature resistance, which are difficult to meet the safe and reliable operation needs of modern power grids.
A heat shrinkable material for cables is used, which consists of polyolefin resin, allyl-containing functionalized ring triphosphazene derivative, peroxide crosslinking agent, halogen-free composite flame retardant filler, crosslinking agent and functional additive. It is prepared by double-roller melt blending, injection molding machine injection, vacuum expansion and other processes to form a material with a tight and stable crosslinking network.
It significantly improves the mechanical properties and heat resistance of heat shrinkable materials for cables, improves flame retardant performance and thermal stability, and can better meet the safe and reliable operation needs of modern power grids.
Smart Images

Figure CN119899445A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material technology, and in particular relates to a heat shrinkable material for cables and a preparation method thereof. Background Art
[0002] In recent years, major accidents caused by problems with cables and accessories have occurred frequently in my country, with economic losses reaching tens of billions of yuan. These accidents not only brought great pain and losses to the victims and their families, but also brought serious safety hazards to society. Therefore, it is particularly important to improve the product quality of cables and accessories and strengthen the maintenance and repair of cables.
[0003] As a high molecular polymer with shape memory properties, heat shrinkable materials can shrink and fit tightly to the surface of objects such as cables after heating treatment, thereby providing insulation, moisture-proof, sealing and protection functions. In the field of power engineering, heat shrinkable materials are widely used in the manufacture of cable accessories. Such materials must have excellent electrical insulation performance, mechanical strength and high temperature resistance to ensure their stable operation in the power system. With its excellent processing performance, excellent thermodynamic properties and superior electrical insulation ability, cross-linked polyethylene has gradually replaced traditional polyvinyl chloride in the wire and cable industry and become an ideal choice of insulation material. However, the common flammability problem of polyolefin polymer materials has largely restricted its application scope. During operation, wires and cables are simultaneously subjected to multiple stresses such as heat, electricity, and mechanical stresses. These factors interact with each other, space charge accumulates, accelerates cable insulation aging, and leads to irreversible damage to polyethylene insulation materials, and even power accidents, which bring hidden dangers to the operation of the power grid. Polyethylene materials are not heat-resistant enough, and their performance is prone to degradation in high temperature environments, such as reduced mechanical strength and poor dimensional stability. This limits the application of polyethylene materials in high temperature environments, such as wires and cables that need to withstand high temperatures. In these fields, polyethylene may not meet the requirements of long-term stability and safety. Therefore, how to improve the heat resistance of cross-linked polyethylene while maintaining the material properties is a difficult problem that needs to be solved urgently.
[0004] In industrial production practice, peroxide crosslinking is currently the most widely used crosslinking technology. Regarding the study of the peroxide crosslinking mechanism, organic peroxides are added to polyethylene resins. At a certain temperature, the organic peroxides decompose into free radicals; these free radicals are highly reactive and can capture hydrogen atoms on the polyethylene molecular chain, turning them into active polyethylene macromolecular free radicals; finally, these active polyethylene macromolecular free radicals will undergo carbon-carbon crosslinking reactions, that is, they will combine with each other to form a planar network structure or a three-dimensional network structure. Compared with other crosslinking processes, the peroxide crosslinking method not only has a faster crosslinking rate, but is also more suitable for large-scale continuous production; and the required equipment occupies a smaller area and has a lower initial investment cost, so it has been widely used in the field of rubber and plastic product processing.
[0005] With the rapid development of the power industry and the continuous advancement of smart grid construction, the comprehensive performance and environmental protection requirements of cable accessories are increasing. Traditional cable accessories have obvious deficiencies in flame retardancy, thermal stability and high temperature resistance, and it is difficult to meet the safe and reliable operation requirements of modern power grids. Therefore, the development of a heat shrink material for cables with excellent flame retardancy, good thermal stability and high temperature resistance has important theoretical significance and practical value for promoting scientific and technological progress in the power industry. Summary of the invention
[0006] The purpose of the embodiments of the present application is to provide a heat shrinkable material for cables, aiming to solve the problem that traditional cable accessories have obvious deficiencies in flame retardancy, thermal stability and high temperature resistance, and are difficult to meet the safe and reliable operation requirements of modern power grids.
[0007] The embodiment of the present application is implemented as follows: a heat shrink material for a cable includes the following raw materials in parts by weight:
[0008] 80-100 parts of polyolefin resin, 5-40 parts of allyl functionalized cyclotriphosphazene derivative, 2-10 parts of peroxide crosslinking agent, 90-120 parts of halogen-free composite flame retardant filler, 0.4-3 parts of auxiliary crosslinking agent and 4-10 parts of functional additive.
[0009] The present application also provides a method for preparing a heat shrinkable material for a cable, comprising:
[0010] The polyolefin resin, the allyl functionalized cyclotriphosphazene derivative, the peroxide crosslinking agent, the halogen-free composite flame retardant filler, the auxiliary crosslinking agent and the functional additive are mixed and added into a double-roll mill for melt blending at a temperature of 110-120° C. until the raw materials are uniformly mixed to obtain a masterbatch;
[0011] The masterbatch is injected into a mold by an injection molding machine, the cross-linking temperature is 150-200° C., the time is 10-20 min, and the pressure is 10-20 MPa to obtain a heat shrinkable preform;
[0012] The heat shrinkable preform is placed in a vacuum expansion device at a temperature of 120-130° C. for 10-20 minutes, the diameter of the heat shrinkable preform is expanded by 2-3 times, and the heat shrinkable material for cable is obtained after cooling and shaping.
[0013] The heat shrink material for cables provided in the embodiments of the present application introduces an allyl functionalized cyclotriphosphazene derivative suitable for peroxide cross-linked polyethylene system into the system, and the molecular chain end thereof contains a large number of allyl functional groups, has high reactivity, and can react with the active sites in the polyethylene molecular chain under the initiation of cross-linking agents such as peroxide, thereby increasing the cross-linking density, forming a more compact and stable cross-linked network, and effectively improving the mechanical properties and heat resistance of the heat shrink material for cables. In addition, the allyl functionalized cyclotriphosphazene derivative acts as both a flame retardant and a co-cross-linking agent in the system, which helps to further improve the comprehensive performance of the cross-linked polyethylene material, especially significantly improving the heat resistance and flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A cross-linking network diagram of the allyl functionalized cyclotriphosphazene derivative in the polyethylene-based insulating heat shrink cap provided in the examples of the present application;
[0015] Figure 2 This is the infrared spectrum of the allyl functionalized cyclotriphosphazene derivative provided in Example 1 of the present application;
[0016] Figure 3 Gel content spectra of heat shrinkable materials for cables provided in Examples 1-6 and Comparative Examples 1-3 of the present application;
[0017] Figure 4 Maximum tensile stress spectra of heat shrinkable materials for cables provided in Examples 1-6 and Comparative Examples 1-3 of the present application;
[0018] Figure 5 The limiting oxygen index spectra of the heat shrinkable materials for cables provided in Examples 1-6 and Comparative Examples 1-3 of the present application;
[0019] Figure 6 This is a scanning electron microscope spectra of the allyl-functionalized cyclotriphosphazene derivative (a) and the heat shrinkable material for cables (b) provided in Example 1 of the present application. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0021] The present application embodiment provides a heat shrinkable material for cables, comprising the following raw materials in parts by weight:
[0022] 80-100 parts of polyolefin resin, 5-40 parts of allyl functionalized cyclotriphosphazene derivative, 2-10 parts of peroxide crosslinking agent, 90-120 parts of halogen-free composite flame retardant filler, 0.4-3 parts of auxiliary crosslinking agent and 4-10 parts of functional additive.
[0023] In some embodiments of the present application, the preparation method of the allyl functionalized cyclotriphosphazene derivative is:
[0024] Under a nitrogen atmosphere, eugenol was dissolved in acetonitrile and stirred for reaction, and then a catalyst was added to obtain a mixed solution;
[0025] preparing an acetonitrile solution containing hexachlorocyclotriphosphazene;
[0026] The acetonitrile solution containing hexachlorocyclotriphosphazene is added dropwise to the mixed solution, reacted at a temperature of 80 to 90° C. for 24 to 52 hours, filtered, and then the acetonitrile is removed by rotary evaporation of the obtained filtrate, and the obtained product is recrystallized from ethanol to obtain an allyl-functionalized cyclotriphosphazene derivative;
[0027] The molar ratio of eugenol to hexachlorocyclotriphosphazene is (0.15-0.3):(0.028-0.031), and the ratio of the raw materials directly affects the yield of the obtained allyl-functionalized cyclotriphosphazene derivative, preferably (0.28-0.3):0.03.
[0028] Wherein, the catalyst is potassium carbonate or a mixture of potassium carbonate and sodium carbonate in a mass ratio of 1:1.
[0029] Wherein, the allyl functionalized cyclotriphosphazene derivative is a compound shown in the following structural formula 1:
[0030]
[0031] The reaction equation of the allyl functionalized cyclotriphosphazene derivative is as follows:
[0032]
[0033] In this application, the above-mentioned allyl functionalized cyclotriphosphazene derivatives are introduced into the peroxide cross-linked polyethylene system. On the one hand, the allyl functional group has a high reactivity and can react with the active sites in the polyethylene molecular chain under the initiation of cross-linking agents such as peroxide, thereby increasing the number of cross-linking points, improving the cross-linking density, and forming a more compact and stable cross-linked network. On the other hand, the allyl functionalized cyclotriphosphazene derivatives are rich in phosphorus and nitrogen elements, which have significant effects in the field of flame retardancy. Phosphorus can promote the formation of a carbon layer during combustion, isolating oxygen and heat; nitrogen can release non-flammable gases, dilute the concentration of combustible gases, and reduce the flame temperature. Therefore, the introduction of allyl cyclotriphosphazene derivatives can significantly improve the flame retardant properties of cross-linked polyethylene. Therefore, the introduction of allyl cyclotriphosphazene derivatives into the cross-linked polyethylene system in this application can improve the heat resistance and flame retardancy of the material. Through the introduction of this modifier, the application field of cross-linked polyethylene materials can be broadened to meet the performance requirements in more specific application scenarios. At the same time, this also provides new ideas and methods for the sustainable development of cross-linked polyethylene materials.
[0034] In some embodiments of the present application, the polyolefin resin includes at least one of low-density polyethylene, ethylene-propylene-diene rubber, ethylene-vinyl acetate copolymer and polyolefin elastomer.
[0035] In some embodiments of the present application, the peroxide cross-linking agent is at least one of dicumyl peroxide, di-tert-butyl peroxide and benzoyl peroxide.
[0036] In some embodiments of the present application, the auxiliary cross-linking agent is at least one of diallyl bismaleate, pentaerythritol tetramethacrylate and triallyl isocyanurate.
[0037] In some embodiments of the present application, the inorganic composite flame retardant filler is at least one of magnesium hydroxide and aluminum hydroxide.
[0038] In some embodiments of the present application, the functional additive is at least one of an antioxidant, a lubricant, and a plasticizer. The antioxidant is at least one of an alkyl biphenyl antioxidant, a hydroxyphosphonate antioxidant, and a hydroxylate antioxidant; the lubricant is at least one of zinc stearate, stearamide, and oleamide; and the plasticizer is at least one of dibutyl phthalate, tricresyl phosphate, and dioctyl phthalate.
[0039] The present application also provides a method for preparing the heat shrinkable material for cables, comprising:
[0040] The polyolefin resin, the allyl functionalized cyclotriphosphazene derivative, the peroxide crosslinking agent, the halogen-free composite flame retardant filler, the auxiliary crosslinking agent and the functional additive are mixed and added into a double-roll mill for melt blending at a temperature of 110-120° C. until the raw materials are uniformly mixed to obtain a masterbatch;
[0041] The masterbatch is injected into a mold by an injection molding machine, the cross-linking temperature is 150-200° C., the time is 10-20 min, and the pressure is 10-20 MPa to obtain a heat shrinkable preform;
[0042] The heat shrinkable preform is placed in a vacuum expansion device at a temperature of 120-130° C. for 10-20 minutes, the diameter of the heat shrinkable preform is expanded by 2-3 times, and the heat shrinkable material for cable is obtained after cooling and shaping.
[0043] The heat shrinkable material for cables provided in the embodiments of the present application can be used not only for the production of cable insulation cap finger sleeves, but also for the production of cable accessories such as cable intermediate connection joints, cable insulation sheds and cable terminal heads. Figure 1 The cross-linking network diagram of the allyl-functionalized cyclotriphosphazene derivative in the polyethylene-based insulating heat shrink cap finger sleeve is shown.
[0044] The heat shrink material for cables and the preparation method thereof are described in detail with specific examples as follows. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are all commercially available unless otherwise specified.
[0045] The specific manufacturer of the low-density polyethylene used in the following examples is LG Chemical, which is not specifically limited here.
[0046] Example 1
[0047] Preparation of allyl functionalized cyclotriphosphazene derivatives:
[0048] (1) In a 1000 mL three-necked flask, nitrogen was passed through the left branch, a glass stopper was tightly plugged into the middle branch, and a condenser was added to the right branch to condense and reflux for 24 h. 0.3 mol of eugenol was dissolved in 300 mL of dry acetonitrile solvent by magnetic stirring; after stirring for sufficient reaction, a mixture of potassium carbonate and sodium carbonate (1:1) was added as a catalyst (0.3 mol); under a N2 atmosphere, the glass stopper of the middle branch of the three-necked flask was removed and a dropping funnel was placed on it;
[0049] (2) preparing 300 mL of dry acetonitrile solution containing 0.03 mol of hexachlorocyclotriphosphazene; pouring the prepared solution into the dropping funnel in (1) and slowly dripping the solution into the reaction flask until it is completely dripped;
[0050] (3) After heating to 85°C and reacting for 24 hours, the mixture in the three-necked flask of (1) was filtered. The solid was an insoluble mixture of potassium carbonate and sodium carbonate. The precipitate was washed five times with acetonitrile, and the filtrate (acetonitrile solution containing the product) was collected. The acetonitrile was removed by rotary evaporation to obtain a black viscous oily liquid product. The product was recrystallized by adding ethanol to a round-bottom flask. Crystals grew overnight and were filtered. The white needle-shaped solid was the product containing an allyl-functionalized cyclotriphosphazene derivative with a yield of 92.3%.
[0051] Preparation of heat shrinkable materials for cables:
[0052] (1) 60 parts of low-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 90 parts of halogen-free composite flame retardant filler, 3.5 parts of zinc stearate, 3.5 parts of dibutyl phthalate, and 10103 parts of antioxidant were mixed uniformly in an internal mixer at a temperature of 135±5°C for 15 minutes; 10 parts of diisopropylbenzene peroxide, 3 parts of triallyl isocyanurate, and 40 parts of allyl functionalized cyclotriphosphazene derivative were added in an open mixer at 115±5°C for mixing, and a masterbatch was obtained after 15 minutes;
[0053] (2) injecting the masterbatch obtained in step (1) into a mold through an injection molding machine, with a crosslinking temperature of 150-200° C., a time of 15 min, and a pressure of 15 MPa;
[0054] (3) The cross-linked heat shrinkable material obtained in step (2) is placed in a vacuum expansion device at a temperature of 125±5°C for 15 minutes, the diameter of the heat shrinkable preform is expanded by 2 times, and the heat shrinkable preform is cooled and shaped to obtain the heat shrinkable material for cable.
[0055] Example 2
[0056] Preparation of allyl functionalized cyclotriphosphazene derivatives:
[0057] (1) In a 1000 mL three-necked flask, nitrogen was passed through the left branch, a glass stopper was tightly plugged into the middle branch, and a condenser was added to the right branch to condense and reflux for 28 h. 0.28 mol of eugenol was dissolved in 250 mL of dry acetonitrile solvent by magnetic stirring; after stirring for sufficient reaction, a mixture of potassium carbonate and sodium carbonate (1:1) was added as a catalyst (0.28 mol); under a N2 atmosphere, the glass stopper of the middle branch of the three-necked flask was removed and a dropping funnel was placed on it;
[0058] (2) preparing 280 ml of a dry acetonitrile solution containing 0.03 mol of hexachlorocyclotriphosphazene; pouring the prepared solution into the dropping funnel in (1) and slowly dripping the solution into the reaction flask until the solution is completely dripped;
[0059] (3) After heating to 85° C. and reacting for 28 hours, the mixture in the three-necked flask of (1) was filtered. The solid was an insoluble mixture of potassium carbonate and sodium carbonate. The precipitate was washed five times with acetonitrile, and the filtrate (acetonitrile solution containing the product) was collected. The acetonitrile was removed by rotary evaporation to obtain a black viscous oily liquid product. The product was recrystallized by adding ethanol to a round-bottom flask. Crystals grew overnight and were filtered. The white needle-shaped solid was the product, an allyl-functionalized cyclotriphosphazene derivative, with a yield of 90.7%.
[0060] Preparation of heat shrinkable materials for cables:
[0061] (1) 60 parts of low-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 100 parts of halogen-free composite flame retardant filler, 2.5 parts of zinc stearate, 2.5 parts of dibutyl phthalate, and 10102 parts of antioxidant were mixed uniformly in an internal mixer at a temperature of 135±5°C for 15 minutes; 6 parts of diisopropylbenzene peroxide, 1.2 parts of triallyl isocyanurate, and 20 parts of allyl functionalized cyclotriphosphazene derivative were added in an open mixer at 115±5°C for mixing, and a masterbatch was obtained after 15 minutes;
[0062] (2) injecting the masterbatch obtained in step (1) into a mold through an injection molding machine, with a crosslinking temperature of 150-200° C., a time of 15 min, and a pressure of 15 MPa;
[0063] (3) The cross-linked heat shrinkable material obtained in step (2) is placed in a vacuum expansion device at a temperature of 125±5°C for 15 minutes, the diameter of the heat shrinkable preform is expanded by 2 times, and the heat shrinkable preform is cooled and shaped to obtain the heat shrinkable material for cable.
[0064] Example 3
[0065] Preparation of allyl functionalized cyclotriphosphazene derivatives:
[0066] (1) In a 1000 mL three-necked flask, nitrogen was passed through the left branch, a glass stopper was tightly plugged into the middle branch, and a condenser was added to the right branch to reflux for 30 h. 0.25 mol of eugenol was dissolved in 200 mL of dry acetonitrile solvent by magnetic stirring; after stirring for sufficient reaction, potassium carbonate (0.25 mol) was added as a catalyst; under a N2 atmosphere, the glass stopper of the middle branch of the three-necked flask was removed and a dropping funnel was placed on it;
[0067] (2) preparing 250 mL of a dry acetonitrile solution containing 0.031 mol of hexachlorocyclotriphosphazene; pouring the prepared solution into the dropping funnel in (1) and slowly dripping the solution into the reaction flask until it is completely dripped;
[0068] (3) After heating to 85°C and reacting for 30 hours, the mixture in the three-necked flask of (1) was filtered. The solid was an insoluble mixture of potassium carbonate and sodium carbonate. The precipitate was washed five times with acetonitrile, and the filtrate (acetonitrile solution containing the product) was collected. The acetonitrile was removed by rotary evaporation to obtain a black viscous oily liquid product. The product was recrystallized by adding ethanol to a round-bottom flask. Crystals grew overnight and were filtered. The white needle-shaped solid was the product, an allyl-functionalized cyclotriphosphazene derivative, with a yield of 87.9%.
[0069] Preparation of heat shrinkable materials for cables:
[0070] (1) 60 parts of low-density polyethylene, 30 parts of EPDM rubber, 110 parts of halogen-free composite flame retardant filler, 2.5 parts of stearamide, 2.5 parts of tricresyl phosphate, and 2 parts of antioxidant A0-30 are mixed uniformly in an internal mixer at a temperature of 135±5°C for 15 minutes; 4.5 parts of di-tert-butyl peroxide crosslinking agent, 0.6 parts of triallyl isocyanurate and 20 parts of allyl functionalized cyclotriphosphazene derivative are added in an open mixer at 115±5°C for mixing, and a masterbatch is obtained after 15 minutes;
[0071] (2) injecting the masterbatch obtained in step (1) into a mold through an injection molding machine, with a crosslinking temperature of 150-200° C., a time of 15 min, and a pressure of 15 MPa;
[0072] (3) The cross-linked heat shrinkable material obtained in step (2) is placed in a vacuum expansion device at a temperature of 125±5°C for 15 minutes, the diameter of the heat shrinkable preform is expanded by 2 times, and the heat shrinkable preform is cooled and shaped to obtain the heat shrinkable material for cable.
[0073] Example 4
[0074] Preparation of allyl functionalized cyclotriphosphazene derivatives:
[0075] (1) In a 1000 mL three-necked flask, nitrogen was passed through the left branch, a glass stopper was tightly plugged into the middle branch, and a condenser was added to the right branch to condense and reflux for 40 h. 0.20 mol of eugenol was dissolved in 180 mL of dry acetonitrile solvent by magnetic stirring; after stirring for sufficient reaction, potassium carbonate (0.22 mol) was added as a catalyst; under a N2 atmosphere, the glass stopper of the middle branch of the three-necked flask was removed and a dropping funnel was placed on it;
[0076] (2) preparing 200 mL of dry acetonitrile solution containing 0.028 mol of hexachlorocyclotriphosphazene; pouring the prepared solution into the dropping funnel in (1) and slowly dripping the solution into the reaction flask until it is completely dripped;
[0077] (3) After heating to 85° C. and reacting for 40 hours, the mixture in the three-necked flask of (1) was filtered. The solid was an insoluble mixture of potassium carbonate and sodium carbonate. The precipitate was washed five times with acetonitrile, and the filtrate (acetonitrile solution containing the product) was collected. The acetonitrile was removed by rotary evaporation to obtain a black viscous oily liquid product. The product was recrystallized by adding ethanol to a round-bottom flask. Crystals grew overnight and were filtered. The white needle-shaped solid was the product containing an allyl-functionalized cyclotriphosphazene derivative with a yield of 81.7%.
[0078] Preparation of heat shrinkable materials for cables:
[0079] (1) 60 parts of low-density polyethylene, 30 parts of EPDM rubber, 120 parts of halogen-free composite flame retardant filler, 1.5 parts of stearamide, 1.5 parts of tricresyl phosphate, and 1.2 parts of antioxidant A0-30 were mixed uniformly in an internal mixer at a temperature of 135±5°C for 15 minutes; 3 parts of di-tert-butyl peroxide crosslinking agent, 0.6 parts of triallyl isocyanurate and 10 parts of allyl functionalized cyclotriphosphazene derivative were added in an open mixer at 115±5°C for mixing, and a masterbatch was obtained after 15 minutes;
[0080] (2) injecting the masterbatch obtained in step (1) into a mold through an injection molding machine, with a crosslinking temperature of 150-200° C., a time of 15 min, and a pressure of 15 MPa;
[0081] (3) The cross-linked heat shrinkable material obtained in step (2) is placed in a vacuum expansion device at a temperature of 125±5°C for 15 minutes, the diameter of the heat shrinkable preform is expanded by 2 times, and the heat shrinkable preform is cooled and shaped to obtain the heat shrinkable material for cable.
[0082] Example 5
[0083] Preparation of allyl functionalized cyclotriphosphazene derivatives
[0084] (1) In a 1000 mL three-necked flask, nitrogen was passed through the left branch, a glass stopper was tightly plugged into the middle branch, and a condenser was added to the right branch to reflux for 48 h. 0.18 mol of eugenol was dissolved in 150 mL of dry acetonitrile solvent by magnetic stirring; after stirring for sufficient reaction, potassium carbonate (0.20 mol) was added as a catalyst; under a N2 atmosphere, the glass stopper of the middle branch of the three-necked flask was removed and a dropping funnel was placed on it;
[0085] (2) preparing 250 mL of a dry acetonitrile solution containing 0.03 mol of hexachlorocyclotriphosphazene; pouring the prepared solution into the dropping funnel in (1) and slowly dripping the solution into the reaction flask until it is completely dripped;
[0086] (3) After heating to 55° C. and reacting for 48 hours, the mixture in the three-necked flask of (1) was filtered. The solid was an insoluble mixture of potassium carbonate and sodium carbonate. The precipitate was washed five times with acetonitrile, and the filtrate (acetonitrile solution containing the product) was collected. The acetonitrile was removed by rotary evaporation to obtain a black viscous oily liquid product. The product was recrystallized by adding ethanol to a round-bottom flask. Crystals grew overnight and were filtered. The white needle-shaped solid was the product, an allyl-functionalized cyclotriphosphazene derivative, with a yield of 80.2%.
[0087] Preparation of heat shrinkable materials for cables:
[0088] (1) 60 parts of low-density polyethylene, 20 parts of polyolefin elastomer, 120 parts of halogen-free composite flame retardant filler, 1.5 parts of oleamide, 1.5 parts of dioctyl phthalate, and 1681.2 parts of antioxidant were mixed uniformly in an internal mixer at a temperature of 135±5°C for 15 minutes; 2 parts of diisopropylbenzene peroxide crosslinking agent, 0.4 parts of triallyl isocyanurate, and 10 parts of allyl functionalized cyclotriphosphazene derivative were added in an open mixer at 115±5°C for mixing, and a masterbatch was obtained after 15 minutes;
[0089] (2) injecting the masterbatch obtained in step (1) into a mold through an injection molding machine, with a crosslinking temperature of 150-200° C., a time of 15 min, and a pressure of 15 MPa;
[0090] (3) The cross-linked heat shrinkable material obtained in step (2) is placed in a vacuum expansion device at a temperature of 125±5°C for 15 minutes, the diameter of the heat shrinkable preform is expanded by 2 times, and the heat shrinkable preform is cooled and shaped to obtain the heat shrinkable material for cable.
[0091] Example 6
[0092] Preparation of allyl functionalized cyclotriphosphazene derivatives:
[0093] (1) In a 1000 mL three-necked flask, nitrogen was passed through the left branch, a glass stopper was tightly plugged into the middle branch, and a condenser was added to the right branch to condense and reflux for 52 h. 0.15 mol of eugenol was dissolved in 150 mL of dry acetonitrile solvent by magnetic stirring; after stirring for sufficient reaction, potassium carbonate (0.18 mol) was added as a catalyst; under a N2 atmosphere, the glass stopper of the middle branch of the three-necked flask was removed and a dropping funnel was placed on it;
[0094] (2) preparing 250 mL of a dry acetonitrile solution containing 0.029 mol of hexachlorocyclotriphosphazene; pouring the prepared solution into the dropping funnel in (1) and slowly dripping the solution into the reaction flask until the solution is completely dripped;
[0095] (3) After heating to 55°C and reacting for 52 hours, the mixture in the three-necked flask of (1) was filtered. The solid was an insoluble mixture of potassium carbonate and sodium carbonate. The precipitate was washed five times with acetonitrile, and the filtrate (acetonitrile solution containing the product) was collected. The acetonitrile was removed by rotary evaporation to obtain a black viscous oily liquid product. The product was recrystallized by adding ethanol to a round-bottom flask. Crystals grew overnight and were filtered. The white needle-shaped solid was the product containing an allyl-functionalized cyclotriphosphazene derivative with a yield of 79.6%.
[0096] Preparation of heat shrinkable materials for cables:
[0097] (1) 60 parts of low-density polyethylene, 20 parts of polyolefin elastomer, 140 parts of halogen-free composite flame retardant filler, 1.5 parts of oleamide, 1.5 parts of dioctyl phthalate, and 1681.2 parts of antioxidant were mixed uniformly in an internal mixer at a temperature of 135±5°C for 15 minutes; 2 parts of diisopropylbenzene peroxide crosslinking agent, 0.4 parts of triallyl isocyanurate, and 5 parts of allyl functionalized cyclotriphosphazene derivative were added in an open mixer at 115±5°C for mixing, and a masterbatch was obtained after 15 minutes;
[0098] (2) injecting the masterbatch obtained in step (1) into a mold through an injection molding machine, with a crosslinking temperature of 150-200° C., a time of 15 min, and a pressure of 15 MPa;
[0099] (3) The cross-linked heat shrinkable material obtained in step (2) is placed in a vacuum expansion device at a temperature of 125±5°C for 15 minutes, the diameter of the heat shrinkable preform is expanded by 2 times, and the heat shrinkable preform is cooled and shaped to obtain the heat shrinkable material for cable.
[0100] Comparative Example 1
[0101] Preparation of heat shrinkable materials for cables (excluding allyl functionalized cyclotriphosphazene derivatives):
[0102] (1) 60 parts of low-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, 120 parts of halogen-free composite flame retardant filler, 1.5 parts of zinc stearate, 1.5 parts of dibutyl phthalate, and 1.2 parts of antioxidant 1010 were mixed uniformly in an internal mixer at a temperature of 135±5°C for 15 minutes; 4.5 parts of diisopropyl peroxide crosslinking agent and 0.8 parts of triallyl isocyanurate were added in an open mixer at 115±5°C for mixing, and a masterbatch was obtained after 15 minutes;
[0103] (2) injecting the masterbatch obtained in step (1) into a mold through an injection molding machine, with a crosslinking temperature of 150-200° C., a time of 15 min, and a pressure of 15 MPa;
[0104] (3) The cross-linked heat shrinkable material obtained in step (2) is placed in a vacuum expansion device at a temperature of 125±5°C for 15 minutes, the diameter of the heat shrinkable preform is expanded by 2 times, and the heat shrinkable preform is cooled and shaped to obtain the heat shrinkable material for cable.
[0105] Comparative Example 2
[0106] Preparation of heat shrinkable materials for cables (excluding allyl functionalized cyclotriphosphazene derivatives):
[0107] (1) 60 parts of low-density polyethylene, 30 parts of EPDM rubber, 120 parts of halogen-free composite flame retardant filler, 1.5 parts of zinc stearate, 1.5 parts of dibutyl phthalate, and 1.2 parts of antioxidant 1010 were mixed uniformly in an internal mixer at a temperature of 135±5°C for 15 minutes; 3 parts of di-tert-butyl peroxide crosslinking agent and 0.6 parts of triallyl isocyanurate were added in an open mixer at 115±5°C for mixing, and a masterbatch was obtained after 15 minutes;
[0108] (2) injecting the masterbatch obtained in step (1) into a mold through an injection molding machine, with a crosslinking temperature of 150-200° C., a time of 15 min, and a pressure of 15 MPa;
[0109] (3) The cross-linked heat shrinkable material obtained in step (2) is placed in a vacuum expansion device at a temperature of 125±5°C for 15 minutes, the diameter of the heat shrinkable preform is expanded by 2 times, and the heat shrinkable preform is cooled and shaped to obtain the heat shrinkable material for cable.
[0110] Comparative Example 3
[0111] Preparation of heat shrinkable materials for cables (excluding allyl functionalized cyclotriphosphazene derivatives):
[0112] (1) 60 parts of low-density polyethylene, 20 parts of polyolefin elastomer, 120 parts of halogen-free composite flame retardant filler, 1.5 parts of zinc stearate, 1.5 parts of dibutyl phthalate, and 1.2 parts of antioxidant 1010 were mixed uniformly in an internal mixer at a temperature of 135±5°C for 15 minutes; 2 parts of diisopropyl peroxide crosslinking agent and 0.4 parts of triallyl isocyanurate were added in an open mixer at 115±5°C and mixed for 15 minutes to obtain a masterbatch;
[0113] (2) injecting the masterbatch obtained in step (1) into a mold through an injection molding machine, with a crosslinking temperature of 150-200° C., a time of 15 min, and a pressure of 15 MPa;
[0114] (3) The cross-linked heat shrinkable material obtained in step (2) is placed in a vacuum expansion device at a temperature of 125±5°C for 15 minutes, the diameter of the heat shrinkable preform is expanded by 2 times, and the heat shrinkable preform is cooled and shaped to obtain the heat shrinkable material for cable.
[0115] The allyl functionalized cyclotriphosphazene derivative prepared in Example 1 was tested by infrared spectroscopy. The corresponding infrared spectrum is shown in FIG. Figure 2 shown.
[0116] The gel content, maximum tensile stress, elongation at break and limiting oxygen index of the heat shrinkable materials for cables prepared in the above Examples 1-6 and Comparative Examples 1-3 at different crosslinking temperatures were tested. The test results are shown in Tables 1-2 and Figure 3-5 shown.
[0117] The allyl functionalized cyclotriphosphazene derivative and the heat shrinkable material for cables prepared in Example 1 were tested by scanning electron microscopy. The scanning electron microscopy spectrum is shown in FIG. Figure 6 shown.
[0118] Table 1
[0119]
[0120]
[0121] Table 2
[0122]
[0123] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
[0124] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A heat shrink material for a cable, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of polyolefin resin, 5-40 parts of allyl functionalized cyclotriphosphazene derivative, 2-10 parts of peroxide crosslinking agent, 90-120 parts of halogen-free composite flame retardant filler, 0.4-3 parts of auxiliary crosslinking agent and 4-10 parts of functional additive.
2. The heat shrinkable material for cables according to claim 1, characterized in that: The preparation method of the allyl functionalized cyclotriphosphazene derivative is as follows: Under a nitrogen atmosphere, eugenol was dissolved in acetonitrile and stirred for reaction, and then a catalyst was added to obtain a mixed solution; preparing an acetonitrile solution containing hexachlorocyclotriphosphazene; The acetonitrile solution containing hexachlorocyclotriphosphazene is added dropwise to the mixed solution, reacted at a temperature of 80 to 90° C. for 24 to 52 hours, filtered, and then the acetonitrile is removed by rotary evaporation of the obtained filtrate, and the obtained product is recrystallized from ethanol to obtain an allyl-functionalized cyclotriphosphazene derivative; The molar ratio of eugenol to hexachlorocyclotriphosphazene is (0.15-0.3):(0.028-0.031).
3. The heat shrinkable material for cables according to claim 2, characterized in that: The catalyst is potassium carbonate or a mixture of potassium carbonate and sodium carbonate in a mass ratio of 1:
1.
4. The heat shrinkable material for cables according to claim 2, characterized in that: The molar ratio of eugenol to hexachlorocyclotriphosphazene is (0.28-0.3):0.
03.
5. The heat shrinkable material for cables according to claim 1, characterized in that: The polyolefin resin includes at least one of low-density polyethylene, ethylene-propylene-diene rubber, ethylene-vinyl acetate copolymer and polyolefin elastomer.
6. The heat shrinkable material for cables according to claim 1, characterized in that: The peroxide crosslinking agent is at least one of dicumyl peroxide, di-tert-butyl peroxide and benzoyl peroxide.
7. The heat shrinkable material for cables according to claim 1, characterized in that: The auxiliary cross-linking agent is at least one of diallyl bismaleate, pentaerythritol tetramethacrylate and triallyl isocyanurate.
8. The heat shrinkable material for cables according to claim 1, characterized in that: The inorganic composite flame retardant filler is at least one of magnesium hydroxide and aluminum hydroxide.
9. The heat shrinkable material for cables according to claim 1, characterized in that: The functional additives are antioxidants, lubricants, plasticizers and toughening agents; Among them, the antioxidant is at least one of alkyl biphenyl antioxidants, hydroxyphosphonate antioxidants, and hydroxylate antioxidants; the lubricant is at least one of zinc stearate, stearamide, and oleamide; and the plasticizer is at least one of dibutyl phthalate, tricresyl phosphate, and dioctyl phthalate.
10. A method for preparing the heat shrinkable material for cables according to claim 1, characterized in that: include: The polyolefin resin, the allyl functionalized cyclotriphosphazene derivative, the peroxide crosslinking agent, the halogen-free composite flame retardant filler, the auxiliary crosslinking agent and the functional additive are mixed and added into a double-roll mill for melt blending at a temperature of 110-120° C. until the raw materials are uniformly mixed to obtain a masterbatch; The masterbatch is injected into a mold by an injection molding machine, the cross-linking temperature is 150-200° C., the time is 10-20 min, and the pressure is 10-20 MPa to obtain a heat shrinkable preform; The heat shrinkable preform is placed in a vacuum expansion device at a temperature of 120-130° C. for 10-20 minutes, the diameter of the heat shrinkable preform is expanded by 2-3 times, and the heat shrinkable material for cable is obtained after cooling and shaping.
Citation Information
Cited By
Peroxide crosslinked polyethylene injection molding material for thermoplastic umbrella skirt and preparation method of peroxide crosslinked polyethylene injection molding material
CN121592101A